STUDY ON THE CORRELATION BETWEEN SELF-ESTEEM, COPING AND CLINICAL SYMPTOMS IN A GROUP OF YOUNG ADULTS: A BRIEF REPORT - Savarese, Giulia; Carpinelli, Luna; Fasano, Oreste; Mollo, Monica; Pecoraro, Nadia; Iannaccone, Antonio (European Scientific Journal, ESJ, 2013)
The aim of this research is to analyze how the experiences and representations of self-esteem correlate with clinical symptoms, as well as specific non-functional coping strategies in order to overcome difficulties in the development of autonomy and decision-making. Data show that the coping resources of individuals are directed more towards the Self than towards the social, sometimes even in terms of preoccupation with the Self and social isolation. Low self-esteem has correlations with somatization. It is especially in the female gender and is related to an image of Self that is not positive.